2013
DOI: 10.1021/ml400378e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of PI3Kα Complexed with PI103 and Its Derivatives: New Directions for Inhibitors Design

Abstract: ABSTRACT:The phosphatidylinositol 3-kinase (PI3K) signaling pathway plays important roles in cell proliferation, growth, and survival. Hyperactivated PI3K is frequently found in a wide variety of human cancers, validating it as a promising target for cancer therapy. We determined the crystal structure of the human PI3Kα−PI103 complex to unravel molecular interactions. Based on the structure, substitution at the R 1 position of the phenol portion of PI103 was demonstrated to improve binding affinity via forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 16 publications
4
91
0
Order By: Relevance
“…11,13 Due to the oncogenic potential of PI3Ka and its negative regulator PTEN, PI3Ka has emerged as an attractive target for anticancer drug design. 14,15 Several chemical scaffolds have been designed and synthesized targeting PI3Ka [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and some of these have been investigated in clinical trials. [31][32][33][34] We previously reported the pharmacophore features for PI3Ka inhibitors and identified potential inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 Due to the oncogenic potential of PI3Ka and its negative regulator PTEN, PI3Ka has emerged as an attractive target for anticancer drug design. 14,15 Several chemical scaffolds have been designed and synthesized targeting PI3Ka [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and some of these have been investigated in clinical trials. [31][32][33][34] We previously reported the pharmacophore features for PI3Ka inhibitors and identified potential inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…And three compounds also displayed moderate to excellent PI3Ka kinase inhibition activity with IC 50 values from 1.805 mM to 2.352 mM. The most promising compound 16i showed good inhibitory activity against mTOR/PI3Ka kinase and good antitumor potency for H460 and PC-3 cell lines with IC 50 values of 0.16 ± 0.03 mM, 2.35 ± 0.19 mM, 1.20 ± 0.23 mM and 0.85 ± 0.04 mM, which were 8.6, >5, 7.9 and 19.1 times more active than compound I (1.37 ± 0.07 mM, >10 mM, 9.52 ± 0.29 mM, 16.27 ± 0.54 mM), respectively. The initial SARs and docking studies showed that the chromone moieties were necessary for the activity of these compounds.…”
Section: Discussionmentioning
confidence: 90%
“…Three compounds (10i,16hei) are more active than compound I against PI3Ka kinase. The most promising compound 16i showed good inhibitory activity against mTOR, PI3Ka kinase and good cytotoxicity for H460 and PC-3 cell lines with IC 50 values of 0.16 ± 0.03 mM, 2.35 ± 0.19 mM, 1.20 ± 0.23 mM and 0.85 ± 0.04 mM, which were 8.6, 7.9 and 19.1 times more active than compound I (1.37 ± 0.07 mM, 9.52 ± 0.29 mM, 16.27 ± 0.54 mM), respectively.…”
Section: Biological Evaluationmentioning
confidence: 92%
See 2 more Smart Citations